Studying Secondary Growth and Bast Fiber Development: The Hemp Hypocotyl Peeks behind the Wall - Behr, Marc; Legay, Sylvain; Žižková, Eva; Motyka, Václav; Dobrev, Petre I; Hausman, Jean-Francois; Lutts, Stanley; Guerriero, Gea (Frontiers in plant science, 2016)
Cannabis sativa L. is an annual herbaceous crop grown for the production of long extraxylary fibers, the bast fibers, rich in cellulose and used both in the textile and biocomposite sectors. Despite being herbaceous, hemp undergoes secondary growth and this is well exemplified by the hypocotyl. The hypocotyl was already shown to be a suitable model to study secondary growth in other herbaceous species, namely Arabidopsis thaliana and it shows an important practical advantage, i.e., elongation and radial thickening are temporally separated. This study focuses on the mechanisms marking the transition from primary to secondary growth in the hemp hypocotyl by analysing the suite of events accompanying vascular tissue and bast fiber development. Transcriptomics, imaging and quantification of phytohormones were carried out on four representative developmental stages (i.e., 6-9-15-20 days after sowing) to provide a comprehensive overview of the events associated with primary and secondary growth in hemp. This multidisciplinary approach provides cell wall-related snapshots of the growing hemp hypocotyl and identifies marker genes associated with the young (expansins, β-galactosidases, and transcription factors involved in light-related processes) and the older hypocotyl (secondary cell wall biosynthetic genes and transcription factors).
Keywords: hypocotyl; bast fibers; RNA-Seq; cell wall; phytohormones; Cannabis sativa; immunohistochemistry